Temporal variations of the oldest Emperor-Hawaiian plume signature influenced by interaction with shallow mantle features - Kempton, Pamela; Adam, C.; Saunders, A. D.; Barry, T. L. (My University, 2025)
Data associated with Kempton et al. (2025) Temporal variations of the oldest Emperor-Hawaiian plume signature influenced by interaction with shallow mantle features. Geochemistry, Geophysics, Geosystems [Paper #2025GC012208] Hawaiian volcanoes < ~7 Ma are believed to be sourced from two different portions of the deep mantle: Loa-trend volcanoes originate from within the Pacific Large Low Shear Velocity Province (LLSVP), whereas Kea-trend volcanoes tap ambient mantle adjacent to the LLSVP. To assess whether the Emperor-Hawaiian plume maintained this association throughout its history, we present new geochemical data (trace elements, Sr-Nd-Pb-Hf isotopes) and geodynamical modelling for Emperor Seamounts ranging from > 81 Ma (Meijii and Detroit Seamounts) to ~50 Ma (Kōko Seamount). We show that Emperor seamounts differ from younger Hawaiian Islands in the abundance of isotopically depleted components. In Hf-Nd isotope space, Detroit lavas trend toward a high Hf component similar to that observed in other mantle plumes (e.g., Iceland, Galapagos). This component originated deep within the mantle, possibly as a sheath surrounding the plume stem. Sampling of this component was facilitated by Detroit being ridge-proximal when it formed (~81 – 76 Ma). Emperor seamounts younger than Suiko (~68 Ma) were intraplate and located beneath progressively older, thicker lithosphere. Backtracked locations of Emperor seamounts lie up to 15o latitude north of the Pacific LLSVP. This suggests the ancestral Emperor-Hawaiian plume was either (i) not initially associated with the Pacific LLSVP. (ii) was deflected northward by shallow mantle features such that plume-ridge interactions dominated in the upper mantle or convective flow patterns modified the plume structure in the mid mantle, or (iii) the edge of the Pacific LLSVP receded southward by more than 15° over the past ~100 m.y.